Kepribadian Sebagai Modal Dasar Untuk Tercapainya Kualitas Kinerja Para Tenaga Kependidikan - Djalali, M. As'ad (ANIMA Indonesian Psychological Journal, 2007)
The low quality of educational professionals is a universal problem found in already developed as well as in developing countries. It is assumed that it is due to the initial low quality of the educators or candidate educators and also because of low financial support. Improvement of hygiene and motivational factors are proposed as betterment especially to enhance work motivation of the educators. Improvement of the selection system beginning from the educational student level is proposed to enhance the quality of the candidate educator. Betterment of the quality of the candidate educator and educators is an unconditional alternative to promote performance. Rendahnya kualitas kerja tenaga kependidikan merupakan problematika universal yang terjadi di negara maju atau berkembang. Hal ini diduga berkaitan dengan rendahnya kualitas awal para pendidik atau calon pendidik serta rendahnya tunjangan finansial. Perbaikan faktor higiene dan motivasional diajukan sebagai tawaran perbaikan khususnya untuk meningkatkan motivasi kerja para pendidik. Perbaikan sistem seleksi mulai dari tingkat mahasiswa kependidikan ditawarkan sebagai solusi perbaikan kualitas calon tenaga pendidik. Perbaikan kualitas calon pendidik serta para tenaga pendidik merupakan suatu pilihan mutlak peningkatan kinerja